Effects of walnut (Juglans regia L.) kernel extract and juglone on dopamine levels and oxidative stress in rats - Cintesun, Sener; Ozman, Zeynep; Kocyigit, Abdurrahim; Mansuroglu, Banu; Kocacaliskan, Ismail (ELSEVIER, 2023)
3,4-dihydroxyphenethylamine (dopamine) is a neurotransmitter that has vital functions in the nervous system. Dopamine metabolism and reactive oxygen species (ROS) production are highly related processes. The present study aims to evaluate the effects of walnut (Juglans regia L.) extract (WE) and 5-hydroxy-1,4 naphthoquinone (juglone) on dopamine levels and oxidative stress. For this purpose, WE and juglone were administered to rats. Serum and brain dopamine levels, total oxidant status (TOS), and total antioxidant status (TAS) were measured after 21 days. The oxidative stress index (OSI) was calculated. WE (300 mg/kg) significantly increased brain dopamine levels. WE and juglone reduced oxidative stress in liver and brain tissues compared to serum. Our results revealed that WE and juglone might have a neuroprotective effect. Further studies are needed to extensively investigate the molecular mechanism of the effects of herbal extracts and phenolic compounds on brain health.
Keywords: Dopamine; Walnut; Juglone; Total antioxidant status; Total oxidant status; Oxidative stress; PHENOLIC-COMPOUNDS; ANTIOXIDANT; Food Science & Technology